The mathematics teacher trainee as an assistant teacher - Szász, Réka (Teaching Mathematics and Computer Science, 2005)
The experiment described in the article aims to answer two needs at once: that of assistant teachers in schools, and that of a more practical training of mathematics teachers. The answer suggested is a model of school experience where mathematics teacher trainees work as assistant teachers in schools. An attempt to realize this model is described, and it is evaluated positively.